Shared Governance in an Adult Education Doctoral Program: “Self-Directed Learning meets Democratic Process” – A Delicate Balance of Intent, Implementation, and Impact - Diane Novak; Philip Moulden; Elizabeth Peterson; Eugene Rinaldi; Nadira K. Charaniya; Susan Malekpour; Diana Churchill; Jo D. Kostka (Adult Education Research Conference, 2008)
This symposium explores the governance component offered within a doctoral program in which students were given the opportunity to engage in collective decision-making through democratic process. Panelists, most of whom were research participants for the dissertation upon which this exploration is based, represent cohort groups from 1996 through 2007.
Keywords: shared governance; adult education; democratic process; doctoral program